Primary testicular lymphoma with solitary cutaneous nodule as the initial presentation - Dalal, Varsha; Kaur, Manveen; Siraj, Fouzia; Singh, Avninder; Bansal, Anju (Canadian Urological Association Journal, 2015)
Primary testicular lymphoma (PTL) is an uncommon disease, and accounts for about 1% to 2% of non-Hodgkin’s lymphomas and less than 5% of all testicular malignancies. Of all testicular malignances, primary testicular diffuse large B-cell lymphoma is the most common type, whose incidence is estimated at 0.26/100 000 per year. At presentation or relapse, PTL tends to spread to several extranodal sites, such as the contralateral testis, the central nervous system, skin, lung, pleura, Waldeyer’s ring, and soft tissues. Orchiectomy and chemotherapy are the preferred treatment. We report a case of a 40-year-old male presenting with a nodule on the anterior abdominal wall and with right scrotal swelling on physical examination. Histopathologic examination led to the diagnosis of cutaneous metastasis of testicular lymphoma.